Socioterminology and its variability and polysemy in real use - Karimbaeva, Asal (The Lingua Spectrum, 2025)
This paper explores socioterminology as an inquiry into how terms actually live in discourse, contrasting the ideal of one-concept–one-term with the realities of variation, polysemy, metaphorical extension, and register-driven shifts. Drawing on sociocognitive terminology (Temmerman, 2000), the Wüsterian tradition and its critiques (Cabré, 1999), and usage-based semantics (Geeraerts, 2010; Langacker, 2008), the narrative shows how communities, professions, and media ecologies enregister terms differently, producing stable cores and fuzzy peripheries. Corpus methods (concordances, collocations, distributional profiles) reveal these dynamics across genres from statutes and standards to news and social media. Bridging the Generative Lexicon’s dot-type intuition with socioterminological evidence, the paper proposes documentation practices for terminography and translation: explicit context features, prototype structuring of senses, and iterative corpus monitoring. The outcome is a pragmatic model that treats polysemy as organized variation to be managed, not eliminated, improving clarity in multilingual communication.